PENGELOLAAN KELAS PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD JAM`IYYATUL HUJJAJ BUKITTINGGI - Mimi Jelita; Junaidi Junaidi; Arifmiboy Arifmiboy; Iswantir iswantir (Universitas Pahlawan Tuanku Tambusai, 2022)
Good classroom management can certainly create and maintain a classroom atmosphere so that teaching and learning activities can take place effectively and efficiently. The formulation of the problem in this study is about how to manage classes in Islamic religious education lessons and the efforts of Islamic religious education teachers in overcoming classroom management problems. This study aims to find out how to manage classes in Islamic religious education lessons and find out how the efforts of Islamic religious education teachers in overcoming problems in classroom management. This type of research is a descriptive qualitative study that describes classroom management on Islamic Religious Education subjects at Jam`iyyatul Hujjaj Elementary School, Bukittinggi. In collecting data the researchers used observation and interview techniques. Meanwhile, to analyze it, the researcher used steps of data reduction, data presentation and drawing conclusions. From the research that has been done, it can be concluded that the way teachers manage the class non-physically is by creating a positive climate in the classroom so that students feel comfortable in the learning process. To create optimal learning conditions, continuously pay attention to the environment in the learning process to create comfortable learning. In terms of maintaining optimal learning conditions the teacher always gives reactions such as giving advice and praise to students according to their activities, while to restore optimal learning conditions the teacher improves student behavior, in modifying student behavior, the teacher advises and teaches good behavior by giving examples and guidance and provide motivation to students. Keywords: Class Management, Islamic Religious Education